2021
DOI: 10.1002/hed.26878
|View full text |Cite
|
Sign up to set email alerts
|

Transoral laser microsurgery in locally advanced laryngeal cancer: Prognostic impact of anterior versus posterior compartments

Abstract: Background: To evaluate the importance of larynx compartments in the prognosis of T3-T4a laryngeal cancer treated with transoral laser microsurgery. Methods: Two hundred and two consecutive pT3-T4a larynx carcinomas. Pre-epiglottic space involvement, anterior and posterior paraglottic space (PGS) involvement, vocal cord, and arytenoid mobility were determined. Local control with laser (LC), overall survival (OS), disease-specific survival (DSS), and laryngectomy-free survival (LFS) were evaluated. Results: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…In a retrospective series of 15 patients treated by salvage TL for recurrences after CO 2 TOLMS, Horwich et al 23 found a high prevalence of cartilage invasion (at the level of the thyroid and cricoid in 66% and 60% of patients, respectively), probably reflecting the three most frequent areas of failure of tumour control by transoral surgery, i.e. the anterior commissure (especially in the presence of transcommissural tumours), the subglottis, and the posterior paraglottic space 5 , 23 . In our series, the rate of invaded cartilages was much lower, presumably indicating that recurrences had been detected earlier, thanks to our proactive policy of systematic imaging follow-up in high-risk T2-T3 glottic cancers 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective series of 15 patients treated by salvage TL for recurrences after CO 2 TOLMS, Horwich et al 23 found a high prevalence of cartilage invasion (at the level of the thyroid and cricoid in 66% and 60% of patients, respectively), probably reflecting the three most frequent areas of failure of tumour control by transoral surgery, i.e. the anterior commissure (especially in the presence of transcommissural tumours), the subglottis, and the posterior paraglottic space 5 , 23 . In our series, the rate of invaded cartilages was much lower, presumably indicating that recurrences had been detected earlier, thanks to our proactive policy of systematic imaging follow-up in high-risk T2-T3 glottic cancers 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Carbon dioxide transoral laser microsurgery (CO 2 TOLMS) as defined by the European Laryngological Society (ELS) 1 is a well-established treatment option for early (T1-T2) and selected T3 glottic tumours [2][3][4][5] . When compared to open surgery, assessment of tumour margins during and after CO 2 TOLMS is hampered by thermal damage and shrinkage of the small specimens, potentially reaching 29% in its anteroposterior length 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The paraglottic space is of utmost importance regarding laryngeal cancer spread 7,8 . The local spread of laryngeal cancer depends primarily on its site of origin, which is predominantly the mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…The paraglottic space is of utmost importance regarding laryngeal cancer spread. 7 , 8 The local spread of laryngeal cancer depends primarily on its site of origin, which is predominantly the mucosa. The route of invasion is highly determined by the anatomy of the adjacent tissues, especially their muscular content.…”
Section: Introductionmentioning
confidence: 99%
“…des Ary kontraindiziert sein kann und andere Möglichkeiten der chirurgischen Tumor Entfernung diskutiert werden müssen, wie eine horizontale supraglottische Teilresektion, eine totale Laryngektomie oder auch ein nichtoperatives Vorgehen mittels Radiochemotherapie [3,4]. In multivariaten Analysen sind die Fixation des Arytenoidgelenks durch eine Tumorinfiltration und die Infiltration des posterioren und inferioren PGR unabhängige Variablen für die lokale Tumorkontrolle [5]. Daher kommt der präthera-…”
unclassified